2003
DOI: 10.2174/1389200033489226
|View full text |Cite
|
Sign up to set email alerts
|

Akt in Prostate Cancer: Possible Role in Androgen-Independence

Abstract: Akt, a downstream effector of phosphatidylinositol 3-kinase (PI3K), has often been implicated in prostate cancer. Studies in prostate tumor cell lines revealed that Akt activation is probably important for the progression of prostate cancer to an androgen-independent state. Investigations of human prostate cancer tissues show that although there is neither Akt gene amplification nor enhanced protein expression in prostate cancer compared to normal tissue, poorly differentiated tumors exhibit increased expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 0 publications
3
75
1
Order By: Relevance
“…Cell line work demonstrates that Akt activity increases during androgen ablation to stimulate cell growth and survival when androgen reliance is weaker, and therefore promote development of HRPC (Gao et al, 2003;Ghosh et al, 2003;Lin et al, 2003). Work using human prostate tissue confirms that pAkt 473 is expressed in PIN and invasive prostate cancer, and staining intensity positively correlated with PSA levels and Gleason grades (Ghosh et al, 2003;Altomare and Testa, 2005;Majumder and Sellers, 2005). In addition, a large study of 640 radical prostatectomy specimens demonstrated that high levels of pAkt was predictive of biochemical recurrence (Ayala et al, 2003).…”
Section: Protein Expression Patternsmentioning
confidence: 90%
See 2 more Smart Citations
“…Cell line work demonstrates that Akt activity increases during androgen ablation to stimulate cell growth and survival when androgen reliance is weaker, and therefore promote development of HRPC (Gao et al, 2003;Ghosh et al, 2003;Lin et al, 2003). Work using human prostate tissue confirms that pAkt 473 is expressed in PIN and invasive prostate cancer, and staining intensity positively correlated with PSA levels and Gleason grades (Ghosh et al, 2003;Altomare and Testa, 2005;Majumder and Sellers, 2005). In addition, a large study of 640 radical prostatectomy specimens demonstrated that high levels of pAkt was predictive of biochemical recurrence (Ayala et al, 2003).…”
Section: Protein Expression Patternsmentioning
confidence: 90%
“…However, during hormone ablation or antihormone treatment, LNCaP cells undergo growth arrest and apoptosis, and Akt activity is upregulated (more than 20-fold higher), resulting in stimulation of cell growth, compensating for the effects of androgen withdrawal (Gao et al, 2003). Data from these experiments suggest that Akt signals for cell growth and survival at low levels of androgen, and therefore may promote development of HRPC (Ghosh et al, 2003;Lin et al, 2003). This is supported by a report that demonstrates that upregulation of the PI3K cascade allows cells to grow in the presence of antiandrogens and contributes to failure of endocrine therapy (Murillo et al, 2001).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The PI3K/Akt pathway plays an important role in regulating prostate cancer cell proliferation (33)(34)(35)(36), and the Notch signaling pathway has been shown to activate Akt (37,38). It is, therefore, reasonable to examine whether the activity of Akt can be enhanced by Jagged1 together with AR, and whether some relationships exist among them to enhance the cyclin B1 expression level as determined in Fig.…”
Section: Jagged1 Together With Ar Enhances the Expression Level Of Cymentioning
confidence: 99%
“…Previous work suggested that rather than inhibit PI3K, the 3-deoxy-PI compounds inhibit the serine/ threonine protein kinase Akt by binding tightly to its PH domain, which normally binds PI(3,4) P 2 or PI (3,4,5), and trapping it in the cytoplasm, thereby preventing phosphorylation by effector kinases. 7 The spectrum of changes in cells caused by these 3-deoxy-PI molecules differs from other widely studied cell growth inhibitors.…”
Section: Introductionmentioning
confidence: 99%